The impact of electronic commerce adoption on the performance of microenterprises: Do technological context, organizational context, and external environment matter? - Suyanto Suyanto; Arvin Winatha; Olivia Tanaya (Problems and Perspectives in Management)
Electronic commerce is gaining importance as a hub for product sourcing, helping businesses earn a competitive edge, and connecting with consumers. Despite its enormous benefits, very few microenterprises in Indonesia adopted electronic commerce. This study analyzes three determinants influencing electronic commerce adoption in microenterprises and evaluates the impacts of these three determinants on firm performance. The paper adopts the TOE (technology, organization, external environment) framework. The quantitative explanatory method uses a questionnaire distributed directly to 113 Indonesian microenterprises’ owners registered in the database of the East Java Department of Cooperative, Micro, Small, and Medium Enterprises from October 2023 to July 2024. The collected data were processed via structural equation modeling partial least squares (SEM-PLS). The findings indicate that a decision to adopt technology has a direct, positive, and significant impact on the adoption of electronic commerce in Indonesian enterprises. Second, organizational context (such as firm size or age) has a positive and significant effect on the willingness to adopt electronic commerce. Third, the external environment has a positive influence on the adoption of electronic commerce. The results confirm the positive impact of the adoption of electronic commerce on the performance of Indonesian microenterprises. These findings justify the importance of TOE contexts in supporting electronic commerce adoption in Indonesian microenterprises and, in turn, increase the performance of the corresponding micro-firms. Acknowledgment This work was supported by the Indonesian Ministry of Education, Culture, Research, and Technology under fundamental research grant number 109/E5/PG.02.00.PL/2024.The authors do not have permission to share the data because the raw data are collected under a license from the East Java Department of Cooperative, Micro, Small, and Medium Enterprises.